The effect of procedural fairness and supervisor support in the relationship between job insecurity and organizational citizenship behavior - Andrés López Bohle, Sergio; Ramón Mladinic Alonso, Antonio (Review of Business Management, 2017)
Purpose – The aim of this paper is to examine whether the perception of job insecurity negatively affects procedural fairness, which may relate to the Organizational Citizenship Behavior (OCB). Finally, we have tested whether perceived supervisor support has a moderating effect in the relationship between procedural fairness and OCB. Design/methodology/approach – Data were collected from a sample of 707 employees in a metal-mechanic company in Chile. Regression analysis was used to analyze the mediating and moderating effects. Findings – It was found that procedural fairness fully mediates the relationship between Job Insecurity and OCB, such that Job Insecurity is negatively related to procedural fairness, which in turn is positively related to OCB. Also, perceived supervisor support moderates the relationship between procedural fairness and OCB. Originality/value – The paper provides new theoretical insights on the effects that perceived job insecurity has on OCB, giving an empirical insight of the mediator and moderator effects that aid in the comprehension of this relationship.